Molecular Docking Senyawa Heparan Sulfate dan Hyaluronic Acid Lendir Bekicot (Lissachatina fulica) terhadap Reseptor TGF-β pada Proses Penyembuhan Luka - Kuni Afifah; Latifah Nurul Aulia; Rochmatul Fitri; Erlix R Purnama (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
Land snails, commonly known as snails (Lissachatina fulica), produce slime or mucus containing Heparan sulfate and Hyaluronic acid compounds which can speed up the wound healing process by helping the blood clotting process and fibroblast proliferation. This study aims to determine the effectiveness of Heparan sulfate and Hyaluronic acid compounds in snail (Lissachatina fulica) mucus which have the potential to help the wound healing process using the TGF-β receptor and the comparison drug Bioplacenton. This research is an observational study using a docking method between the target protein, namely the TGF-β receptor, and the compounds Heparan sulfate, Hyaluronic acid and Neomycin sulfate. The research stages carried out included target prediction, preparation and 3-dimensional structure of the TGF-β protein, preparation and minimization of compound ligands, docking of test ligands against the TGF-β receptor, visualization and analysis of in silico test data in a qualitative descriptive manner. The results of this research show that the Heparan sulfate compound in Snail Mucus (Lissachatina fulica) is more effective as a wound healing medicine compared to hyaluronic acid and can be used as an alternative wound medicine to replace Neomycin sulfate (Bioplacenton medicine).